Functional Visual Acuity in Age-Related Macular Degeneration. Issue 1 (January 2016) - Tomita, Yohei; Nagai, Norihiro; Suzuki, Misa; Shinoda, Hajime; Uchida, Atsuro; Mochimaru, Hiroshi; Izumi-Nagai, Kanako; Sasaki, Mariko; Tsubota, Kazuo; Ozawa, Yoko
ABSTRACT: Purpose: We evaluated whether a functional visual acuity (FVA) system can detect subtle changes in central visual acuity that reflect pathological findings associated with age-related macular degeneration (AMD). Methods: Twenty-eight patients with unilateral AMD and logMAR monocular best corrected VA better than 0 in both eyes, as measured by conventional chart examination, were analyzed between November 2012 and April 2013. After measuring conventional VA, FVA, and contrast VA with best correction, routine eye examinations including spectral domain–optical coherence tomography were performed. Standard Schirmer test was performed, and corneal and lens densities were measured. Results: The FVA score (p < 0.001) and visual maintenance ratio (p < 0.001) measured by the FVA system, contrast VA (p < 0. 01), and conventional VA (p < 0.01) were significantly worse in the AMD-affected eyes than in the fellow eyes. No significant differences were observed in the anterior segment conditions. Forward stepwise regression analysis demonstrated that the length of interdigitation zone disruption, as visualized by optical coherence tomography imaging, correlated with the FVA score (p < 0.01) but not with any other parameters investigated. Conclusions: The FVA system detects subtle changes in best corrected VA in AMD-affected eyes and reflects interdigitation zone disruption, an anatomical change in the retina recorded by optical coherence tomography. Further studies are required to understand the value of the FVA system in detecting subtle changes in AMD.